2009
DOI: 10.1152/ajplung.00045.2009
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-mediated lung permeability and host defense proteins

Abstract: Neutrophil recruitment to the alveolar space is associated with increased epithelial permeability. The present study investigated in mice whether neutrophil recruitment to the lung leads to accumulation of plasma-derived host defense proteins in the alveolar space and whether respiratory burst contributes to this increase in permeability. Albumin, complement C1q, and IgM were increased in bronchoalveolar lavage (BAL) fluid 6 h after intratracheal LPS challenge. Neutrophil depletion before LPS treatment complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 45 publications
3
21
0
1
Order By: Relevance
“…The association between levels of extracellular gC1qR and increased chemotaxis is mainly due to the fact that gC1qR can simultaneously bind to neutrophils. The role of C1q in chemotaxis is further confirmed through a study in which the lung epithelial permeability was observed to increase following neutrophil recruitment to the site of accumulation of a number of proteins that included albumin, C1q and IgM [26]. C1q has also been implicated in triggering the production of superoxide (O 2 -) by neutrophils [27].…”
Section: Role Of C1q In Various Cell Processesmentioning
confidence: 87%
“…The association between levels of extracellular gC1qR and increased chemotaxis is mainly due to the fact that gC1qR can simultaneously bind to neutrophils. The role of C1q in chemotaxis is further confirmed through a study in which the lung epithelial permeability was observed to increase following neutrophil recruitment to the site of accumulation of a number of proteins that included albumin, C1q and IgM [26]. C1q has also been implicated in triggering the production of superoxide (O 2 -) by neutrophils [27].…”
Section: Role Of C1q In Various Cell Processesmentioning
confidence: 87%
“…ALI at the early stage is characterized by disruption of microvascular endothelium barrier, leakage of protein‐rich fluid into the interstitium and alveolar space, and extensive release of cytokines, and migration of neutrophils . Previous clinical studies showed that the agents directing against only a single insult, such as increased adhesion molecules, TNF‐ α or interleukin ‐1 β release, and ROS production, do not improve the outcome of the patients .…”
Section: Discussionmentioning
confidence: 99%
“…DCs were infected with opsonized HIV-1, 1 mg/ml (p24 equivalent/ml), for 2 h prior to infection with opsonized M. tuberculosis (MOI 1). The rationale for opsonizing HIV and M. tuberculosis is that in the host pathogens are naturally opsonized by bodily fluids, and in tissues, during infection (23)(24)(25). Furthermore, HIV uses complement opsonization to enhance infection of immature DCs (26), that is, complement opsonization functioning as an immune evasion mechanism to establish infection in a silent manner (27).…”
Section: Infection Of Dcs and Coculture With M Tuberculosis Ag-specimentioning
confidence: 99%